2016
DOI: 10.3109/03639045.2016.1160107
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced topical delivery of tacrolimus by a carbomer hydrogel formulation with transcutol P

Abstract: Tacrolimus (TAC), a non-steroidal anti-inflammatory and immunosuppressive agent, is used for the treatment of atopic dermatitis (AD) and skin immune diseases. TAC-loaded topical hydrogel formulations composed of carbomer, carnosine, transcutol P (diethylene glycol monoethyl ether) and humectant were prepared. For comparison, TAC-loaded topical cream-type formulations were also prepared and commercially available TAC ointment was used as a reference. A drug release study in vitro revealed that the total amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…We innovatively chose MCE (menthol/camphor, 3/1, w/w) as the oil phase of FK506 ME. Moreover, our previous report demonstrated that transcutol P and Cremophor EL possessed good solubilizing capacity on FK506, and Lee et al had certified that transcutol P possessed penetration-enhancing effect, nontoxic property, and biocompatibility with the skin on FK506 36. Therefore, Cremophor EL and transcutol P were chosen as the surfactant and co-surfactant, respectively, in FK506 MCE ME formulation.…”
Section: Resultsmentioning
confidence: 99%
“…We innovatively chose MCE (menthol/camphor, 3/1, w/w) as the oil phase of FK506 ME. Moreover, our previous report demonstrated that transcutol P and Cremophor EL possessed good solubilizing capacity on FK506, and Lee et al had certified that transcutol P possessed penetration-enhancing effect, nontoxic property, and biocompatibility with the skin on FK506 36. Therefore, Cremophor EL and transcutol P were chosen as the surfactant and co-surfactant, respectively, in FK506 MCE ME formulation.…”
Section: Resultsmentioning
confidence: 99%
“…Sample (1 mL) was removed at a predetermined time and reloaded with fresh media. The cumulative amount of drug permeation as a function of time along with flux (J) was statistically determined using HPLC analysis [1,6,27].…”
Section: In Vitro Permeation Studiesmentioning
confidence: 99%
“…Thus, ME-based hydrogels (MEHs) have attracted interest as an alternative topical delivery system [15] , [17] , [20] , [21] . In general, MEHs with a suitable viscosity and good biocompatibility can prolong the retention time of drug on the skin and reduce the risk of skin irritation after their topical application [22] , [23] .…”
Section: Introductionmentioning
confidence: 99%